SMS picture messaging as an adjunct in emergency medicine training – pilot project on feasibility in an African healthcare system - R. Lynch*; A. Moore; M. Barlow; J. O’Sullivan (African Journal of Emergency Medicine, 2013)
Advances in mobile phone technology have aided the development of new methods of instantaneous communication, such as SMS picture messaging. Aims: To assess the feasibility of SMS picture messaging as an adjunct in Emergency Medicine (EM) training and identify factors which might impact on its use in Africa. Methods: Pilot project involving fifteen doctors and 10 nurses in an Irish Emergency Department. SMS picture messages, with predetermined learning points, were sent to all participants on Mondays, Wednesdays and Fridays over an eight week period. All participants were asked to submit an answer to each question. Reminders were sent after 24 h to all non-responders. Discussion: Overall satisfaction among participants was very high. The response rate among doctors (70%) exceeded that for nurses (40%). Conclusion: This pilot project proved very popular with participants and trainers. Technical issues proved frustrating at times and together with cost are likely to pose difficulties for its widespread use in EM training in Africa. It is worthwhile exploring this further.